DAMPAK STRATEGIS PROGRAM CSR TERHADAP KINERJA MEREK, EKUITAS MEREK DAN REPUTASI PERUSAHAAN DI NEGERA BERKEMBANG : PENGUJIAN TERHADAP TEORI META ANALISIS - Ahmad Hermanto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
Currently CSR is a sustainable development strategy for the distribution of welfare of the people in various countries around the world through corporation activity. Therefore, on the effort of increasing welfare of nation state, government establishes the development model towards CSR corporation program as the spreading welfare strategy. This study seeks to investigate whether the strategic effect of CSR program activities on brand performance, industrial brand equity and corporate reputation in order to understand the real effects of actual CSR activities. This research to investigate and treat CSR as a whole construct on CSR program activities which covers several dimensions such as economic, social, and environmental. Specifically, this study test a meta-model of CSR. It is expected to become the basis of measurement models which provide valuable input for coping strategies and actions to be taken to reconstruct the CSR strategy and management programs that significantly impact on brand performance, industrial brand equity and corporate reputation in the future. In this study, the importance of this research will be presented for consideration and relevance in the context of future development.